Timing is everything: The when and how of environmentally induced changes in the epigenome of animals - Faulk, Christopher (Landes Bioscience, 2011)
Environmental influence on developmental plasticity impacts a wide diversity of animal life from insects to humans. We now understand the epigenetic basis for many of these altered phenotypes. The five environmental factors of nutrition, behavior, stress, toxins and stochasticity work individually and in concert to affect the developing epigenome. During early embryogenesis, epigenetic marks, such as DNA methylation, are reset at specific times. Two waves of global demethylation and reestablishment of methylation frame the sensitive times for early environmental influences and will be the focus of this review. Gene transcription, translation and post-translational modification of chromatin remodeling complexes are three mechanisms affected by developmental exposure to environmental factors. To illustrate how changes in the early environment profoundly affect these mechanisms, we provide examples throughout the animal kingdom. Herein we review the history, time points and mechanisms of epigenetic gene-environment interaction.